Highly stretchable electromagnetic interference (EMI) shielding segregated polyurethane/carbon nanotube composites fabricated by microwave selective sintering. Issue 26 (7th June 2019) - Feng, Dong; Xu, Dawei; Wang, Qingqing; Liu, Pengju
Abstract : Microwave selective sintering is a green and efficient strategy to construct a segregated conductive network. Abstract : The formation of a segregated structure in conductive polymer composites (CPCs) is one of the most promising strategies for achieving good electrical conductivity and electromagnetic interference (EMI) shielding performance. Nevertheless, the segregated CPCs usually suffer from deteriorated mechanical properties due to the limited interfacial interaction between polymer granules hindered by the conductive layer. We propose a novel sintering method utilizing the intense selective heating of conductive fillers upon microwave irradiation, which shows obvious advantages over conventional compression molding (CM). To do so, carbon nanotubes (CNTs) were used as microwave absorbers in the thermoplastic polyurethane (TPU) media. Upon irradiation, CNTs were responsible for a local temperature increasing spot on the surface of TPU granules, promoting the molecular diffusion among TPU only in the interface region without damaging the segregated structure. In this way, the elongation at break of the as-prepared TPU/CNT composites reached 350%, approximately ten times higher than that of the composites prepared by the conventional CM. Meanwhile, the microwave sintering (MS) composites showed comparable electrical conductivity and EMI shielding effectiveness (SE) to the CM samples. Our current efforts provide an insight into the development of a highly stretchable EMI shielding material via the "green" method.